Neuroanatomy of Human Brain Development - Pratik Mukherjee; Julia P. Owen; Hao Huang (Frontiers Media SA, 2021)
The human brain is extraordinary complex and yet its origin is a simple tubular structure. Rapid and dramatic structural growth takes place during the fetal and perinatal period. By the time of birth, a repertoire of major cortical, subcortical and white matter structures resembling the adult pattern has emerged, however there are continued maturational changes of the gray matter and white matter throughout childhood and adolescence and into adulthood. The maturation of neuronal structures provides the neuroanatomical basis for the acquisition and refinement of cognitive functions during postnatal development. Histological imaging has been traditionally dominant in understanding neuroanatomy of early brain development and still plays an unparalleled role in this field. Modern magnetic resonance imaging (MRI) techniques including diffusion MRI, as noninvasive tools readily applied to in vivo brains, have become an important complementary approach in revealing the detailed brain anatomy, including the structural connectivity between brain regions. In this research topic, we presented the most recent investigations on understanding the neuroanatomy and connectivity of human brain development using both histology and MRI. Modern advances in mapping normal developmental brain anatomy and connectivity should elucidate many neurodevelopmental disorders, ranging from rare congenital malformations to common disorders such as autism and attention deficit hyperactivity disorder (ADHD), which is a prerequisite for better diagnosis and treatment of these currently poorly understood diseases.